Taking Others as a Mirror: Contingent Social Comparison Promotes Task Engagement - Wang, Lei; Zhang, Xiaoshuang; Li, Lu; Meng, Liang (Frontiers in Human Neuroscience, 2018)
Social comparison implemented in an informational while not controlling manner can be motivating. In order to directly examine the effect of contingent social comparison on one’s task engagement, we manipulated social comparison in an experimental study and adopted an electrophysiological approach to measure one’ task engagement. In this experiment, we engaged participants in a modified stop-watch (SW) task which requires a button press to stop the watch within a given time interval and instructed the participants to either play alone or simultaneously play with a same-sex counterpart. In the latter case, they could freely solicit feedback on their counterparts' performance besides their own. Enlarged stimulus-preceding negativity (SPN) and error-related negativity (ERN) were observed in the two-player condition, indicating strengthened anticipatory attention toward the task-onset stimulus at the pre-task stage and potentially enhanced performance surveillance during task execution. As a complement, self-report data suggested that participants were more intrinsically motivated to engage in the SW task when contingent social comparison was present. Thus, converging electrophysiological and behavioral evidences suggested the pivotal role of contingent social comparison in promoting self-directed task engagement.